PKM Kelompok Tani Sawit “KUD Kampar” Desa Kampa, Riau - Khairiah, Hanifah; Fatmayati Fatmayati; Nina Veronika; Anna Dhora; Antonius J Sihotang; Nur Ama Deli (Politeknik Kampar, 2023)
Oil palm is a plantation commodity that has a strategic role in Indonesia's economic development. The development of the palm oil industry in Indonesia is inseparable from the role of planting materials used by oil palm plantation farmers. Superior oil palm seedlings are the basic capital to achieve high productivity and quality of palm oil. The use of illegal or careless seedlings can cause a decrease in productivity of up to 50%. In contrast, by using superior quality oil palm seedlings, stable production levels can be guaranteed for 25 years, hence the type and quality of seedlings is a major concern. This community service related to superior seedling selection strategies in order to increase national oil palm productivity was carried out at KUD Kampar. KUD Kampar oversees 20 farmer groups of oil palm farmers in Kampar district, so that through this service it is hoped that the PKM Polytechnic Kampar Team can be a means for oil palm farmers in Kampar Regency to get correct and accurate information about superior oil palm seeds and be able to increase the productivity of the oil palm plantations owned by KUD Kampar farmer groups.